Life dispositions of caregivers of a family member with mental disorder - Ivanova, Elena Mihaylova; Stefanova-Bakracheva, Margarita Angelova; Milanova, Vihra Krumova (Frontiers in Psychiatry, 2025)
BackgroundDespite the shift in the focus observed recently on supporting the family rather than only providing care for its member with a mental disorder, there are still many problems faced by the caregivers leading to dysfunction in families with such a member, both as on family and on individual level.AimThe aim of the present study was to identify similarities and differences in the adjustment pathways of caregivers of a parent or child with mental disorder, as compared to a control group, as well as to determine the specific life dispositions of parents caring for child with mental disorder and of children caring for parent with mental disorder.MethodThe design of the study is cross-sectional, comprising a convenience sample of 167 respondents: 82 parents and 46 children caregivers and 39 respondents in the control group, who were administered eight scales, measuring their life orientation, well-being, meaning in life, preferred coping strategies, self-esteem, social anxiety, and depression.ResultsSignificant differences were reported between the control group and the groups of caregivers in respect to well-being and self-esteem, which were higher among the respondents from the control group. Indicative result was the lack of difference in the level of depression between the control group and the caregivers, revealing the result of self-regulation and the different pathways, leading to it. While parents caring for a child with mental disorder had higher orientation children caring for a parent with a mental disorder appeared to be the most vulnerable group – they were avoidant oriented, had lowest well-being, self-esteem and meaning in life and optimism, lacked positive emotions, reported unsatisfactory relationships, lower engagement, and were in ongoing search for meaning in life, and experienced of loneliness to the greatest extent.ConclusionsThe specific adjustment profiles of parents and children caregivers highlighted their different needs for support. While parents may benefit from informational support and guidance, children may benefit more from motivational support to maintain meaning in life. The outlined individual differences may also contribute to family support and counselling aimed at improving functioning of the family system and the performance of its individual members.